2013
DOI: 10.1186/2051-5960-1-21
|View full text |Cite
|
Sign up to set email alerts
|

MCP-1/CCR2 signaling-mediated astrocytosis is accelerated in a transgenic mouse model of SOD1-mutated familial ALS

Abstract: BackgroundEmerging evidence suggests that innate immunity and increased oxidative stress contribute to pathomechanisms in amyotrophic lateral sclerosis (ALS). The aim of the present study was to verify the involvement of monocyte chemoattractant protein-1 (MCP-1) and its specific CC chemokine receptor 2 (CCR2) in the disease progression of ALS. We here demonstrate the expression state of MCP-1 and CCR2 in lumbar spinal cords of mice overexpressing a transgene for G93A mutant human superoxide dismutase 1 (SOD1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 62 publications
3
25
1
Order By: Relevance
“…CCR2 and its ligand monocyte chemoattractant protein-1 (MCP-1) play a role in the macrophage inflammatory response following PNS injury, and promote nerve regeneration40. CCR2 and MCP-1 have previously been reported to be implicated in both ALS41 and peripheral neuropathies pathogenetic cascade42. Our finding corroborates the hypothesis that defective monocyte/macrophages infiltration at the site of nerve degeneration may be implicated in ALS.…”
Section: Discussionsupporting
confidence: 87%
“…CCR2 and its ligand monocyte chemoattractant protein-1 (MCP-1) play a role in the macrophage inflammatory response following PNS injury, and promote nerve regeneration40. CCR2 and MCP-1 have previously been reported to be implicated in both ALS41 and peripheral neuropathies pathogenetic cascade42. Our finding corroborates the hypothesis that defective monocyte/macrophages infiltration at the site of nerve degeneration may be implicated in ALS.…”
Section: Discussionsupporting
confidence: 87%
“…Between December 5, 2011 and November 22, 2012, a total of 71 participants with ALS were screened, of whom 7 were excluded (see Fig 1B). Of the remaining 64 participants (mean age = 53.3 years; 33 men and 31 women), 33 were allocated to receive BM-MSCs with riluzole treatment (MSC group) and 31 received riluzole alone (control group). A total of 59 participants at 4 months and 56 participants at 6 months were included in the primary efficacy analysis (full analysis set).…”
Section: Resultsmentioning
confidence: 99%
“…Although CCL2, CXCL1, and CXCL2 are in the chemokine family, functions of these cytokines are not considered to be related to chemoattraction in this case because astrocytes are unlikely to be chemoattracted. It has been reported that astrocytes can express CCR2 26 and CXCR2 27 as well as IL-6R 28 , and can exert specific functions via these receptors. Activated astrocytes can release CCL11 29 and G-CSF 30 .…”
Section: Discussionmentioning
confidence: 99%